Optimizing Car Imports in Small Island States - Ramoudith, Shiva; Hosein, Patrick; Blake-Thomas, Kevin (International Journal of Operational Research/Nepal, 2019)
In most Small Island Developing States (SIDS), automobile dealers must import vehicles for sale on a periodic basis. This poses a problem for SIDS as the total demand is limited and the vehicle importation costs can be high since the only delivery option is by ship. We consider this problem for a single dealer in which the importation period is fixed and we use historical data (dates on which vehicles are bought, received and sold) to predict which brands/models should be purchased as well as the quantities of each to purchase using simple exponential smoothing. We demonstrate the potential of this method by investigating the time in which a vehicle spends on the lot as well as the probability of a vehicle being on the lot.